A Note on Corallorhiza trifida Chatel.: A Lesser Known Partial Myco-Heterotrophic Orchid from Himachal Pradesh, Western Himalaya, India - Kumar, Puneet; Singh, Harminder; Jalal, Jeewan Singh (Indian Forester, 2020)
No Abstract.